Gross flows of formal and informal workers in the Mexican labor market - Gallardo del Angel, Roberto (Estudios Económicos de El Colegio de México, 2013)
This paper is an analysis of twelve gross flows of workers in the Mexican labor market considering the condition of informal employment. It also contains a seasonal and cyclical analysis. Flows in and out of inactivity are relatively large. The hazard of employment in the informal sector is higher for male and older workers, while the hazard of economic inactivity is higher for younger and female workers. The gross flows have strong seasonal components and the cyclical analysis shows evidence that all gross flows into and out of unemployment have countercyclical patterns. Female workers are the group that is least affected by the business cycle.